Microstructural evolution and thermal stability of AlCr(Si)N hard coatings revealed by in-situ high-temperature high-energy grazing incidence transmission X-ray diffraction. (March 2020) - Jäger, N.; Meindlhumer, M.; Spor, S.; Hruby, H.; Julin, J.; Stark, A.; Nahif, F.; Keckes, J.; Mitterer, C.; Daniel, R.
Graphical abstract: Abstract: An extensive understanding about the microstructural evolution and thermal stability of the metastable AlCr(Si)N coating system is of considerable importance for applications facing high temperatures, but it is also a challenging task since several superimposed processes simultaneously occur at elevated temperatures. In this work, three AlCr(Si)N coatings with 0 at%., 2.5 at% and 5 at% Si were investigated by in-situ high-temperature high-energy grazing incidence transmission X-ray diffraction (HT-HE-GIT-XRD) and complementary differential scanning calorimetry and thermogravimetric analysis measurements combined with conventional ex-situ X-ray diffraction. The results revealed (i) a change in the microstructure from columnar to a fine-grained nano-composite, (ii) a reduced decomposition rate of CrN to Cr2 N, also shifted to higher onset temperatures from  ~ 1000  ∘ C to above  ~ 1100  ∘ C and (iii) an increase of lattice defects and micro strains resulting in a significant increase of compressive residual strain with increasing Si content. While the Si-containing coatings in the as-deposited state show a lower hardness of 28 GPa compared to AlCrN with 32 GPa, vacuum annealing at  ~ 1100  ∘ C led to an increase in hardness to 29 GPa for the coatings containing Si and a decrease in hardness to 26 GPa for AlCrN. Furthermore, the in-situ HT-HE-GIT-XRD method allowed for simultaneously accessing temperature-dependent variations of the coating microstructure (defect density, grain size), residual strain state and phase stability up to  ~ 1100  ∘ C. Finally, the results established a deeper understanding about the relationships between the elemental composition of the materials, the resulting microstructure including crystallographic phases and residual strain state, and the coating properties from room temperature up to  ~ 1100  ∘ C.